2014
DOI: 10.1007/s40299-014-0221-2
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the TPACK in Game-Based Teaching: Does Instructional Sequence Matter?

Abstract: Previous studies have suggested that understanding the relationships and developmental paths among TPACK constructs plays a crucial role in teachers' TPACK development process. Researchers (Chai et al., Edu Technol Soc 13(4):63-73, 2010) have found that technological knowledge, pedagogical knowledge, and content knowledge are all significant predictors of pre-service teachers' TPACK. Thus, one of the major concerns that educators may have is, which type of knowledge should come first in an educational technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 29 publications
1
7
0
2
Order By: Relevance
“…This finding seems to resonate the study Hsu, Liang, and Su (2015) did. In their study, a group of in-service preschool teachers were trained to implement game-based pedagogy.…”
Section: Findings and Discussionsupporting
confidence: 86%
“…This finding seems to resonate the study Hsu, Liang, and Su (2015) did. In their study, a group of in-service preschool teachers were trained to implement game-based pedagogy.…”
Section: Findings and Discussionsupporting
confidence: 86%
“…While only a handful of the Asian game-based learning literature reviewed for this paper has been formally discussed, it is interesting to note eight of nine articles surveyed were supported with government funding (in addition to those previously cited see also Hooshyar et al 2016;Chuang et al 2015;Wang et al 2016;Hsu, Liang, and Su, 2015;Cheng et al 2012;Liu and Chu 2010). This support tends to speak perhaps to national interests and/or availability of funds to promote this area of research and development.…”
Section: Discussionmentioning
confidence: 85%
“…In the L2 field, some literature already exists that documents the contribution of digital games to learning (Hsu et al 2015). Research on games as learning tools for English as a Foreign Language (EFL) students is quite promising.…”
Section: Ability-in Language User-in Context: Design and Claimsmentioning
confidence: 99%
“…1). Although research carried out to validate it by means of structural equations has shown that some of the interactions between the different levels of "knowledge" are not well understood by teachers (Ay, Karadag & Acat, 2015) and are difficult to establish, the reality is that a variety of studies and meta-analyses have been developed around this proposal (Chai, Koh & Tsai, 2013;Ay, Karada & Bahaddin, 2015;Cabero & Barroso, 2016;Khine, Ali & Afar, 2015;Navío and Barroso, 2016), which indicate its validity and significance for ICT teacher training, proposals that have also been diversified from studies of general use of ICT to specific technologies and specific disciplines (Smith, 2013;Tokmak, Incikabi & Ozgelen, 2013;Hsu & Liang, 2015;Deng, Sing, So, Qian & Chen, 2017;Maor, 2017). A model that has acquired some importance in recent years is the "Technological Pedagogical Content Knowledge" (TPACK) developed by Mishra & Koehler (2006).…”
Section: Some Models and Perspectives For Teacher Training In Ictmentioning
confidence: 99%